2010
DOI: 10.1590/s0085-56262010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Imaturos de Chrismopteryx undularia (Blanchard) (Lepidoptera, Geometridae)

Abstract: ABSTRACT. Immatures of Chrismopteryx undularia (Blanchard) (Lepidoptera, Geometridae). Egg, larva and pupa of Chrismopteryx undularia (Blanchard, 1852) (Lepidoptera, Geometridae, Larentiinae) are described and illustrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Thoracic and abdominal setae with longitudinal carinae and multi-pointed apex (Fig. 15-16) have been also described for the first instar of other members of Ennominae (Macariini: Blaik & Malkiewicz 2003;Boarmiini: Vargas & Parra 2013) and Larentiinae (Vargas et al 2010). Depressed tarsal setae TS3 have been already described for the first instar of Larentiinae (Vargas et al 2013); however, the distal margin sawtoothed, as found here for P. obtusaria, has been not previously reported.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Thoracic and abdominal setae with longitudinal carinae and multi-pointed apex (Fig. 15-16) have been also described for the first instar of other members of Ennominae (Macariini: Blaik & Malkiewicz 2003;Boarmiini: Vargas & Parra 2013) and Larentiinae (Vargas et al 2010). Depressed tarsal setae TS3 have been already described for the first instar of Larentiinae (Vargas et al 2013); however, the distal margin sawtoothed, as found here for P. obtusaria, has been not previously reported.…”
Section: Discussionsupporting
confidence: 70%
“…An increase in the number of some thoracic and abdominal setae following the first larval molt has been described for several species of Geometridae (e.g. : Parra & Henríquez-Rodríguez 1993, Blaik & Malkiewicz 2003, Vargas et al 2010, Vargas & Parra 2013. However, this increase is remarkable in the SV group of A6 in the Nearctic species of Pero, reaching a few tens of setae on the external surface of the proleg of A6 of the last instars of some species (McGuffin 1963).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation